Organisational behaviour in the public sector : a critical introduction - Fenwick, John (Professor of Public management) (Emerald points., 2021)
This book adopts a highly critical approach to the ways in which organisations have been analysed by orthodox theories and offers instead a perspective on elements of organisational behaviour including leadership and its failures, structures, cultures, bullying and the denial of individual voice.